1996
DOI: 10.1200/jco.1996.14.2.514
|View full text |Cite
|
Sign up to set email alerts
|

Phase II trial of fludarabine monophosphate as first-line treatment in patients with advanced follicular lymphoma: a multicenter study by the Groupe d'Etude des Lymphomes de l'Adulte.

Abstract: These results confirm that fludarabine is active when used as first-line treatment in patients with follicular lymphoma and has a low toxicity rate. It may be used as single treatment in elderly patients. Associations of fludarabine with other drugs active against follicular lymphoma need to be determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
51
0

Year Published

1998
1998
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(51 citation statements)
references
References 10 publications
0
51
0
Order By: Relevance
“…In a phase II trial of 54 patients reported by Solal-Celigny et al (1996), the overall response rate to fludarabine was 65%, and in the Intergroup randomised trial comparing CVP to fludarabine, the overall response to fludarabine was 69% (Marcus et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a phase II trial of 54 patients reported by Solal-Celigny et al (1996), the overall response rate to fludarabine was 65%, and in the Intergroup randomised trial comparing CVP to fludarabine, the overall response to fludarabine was 69% (Marcus et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Nucleoside analogues such as fludarabine offer an alternative, noncrossresistant option. Fludarabine has been shown to be effective in low-grade nonHodgkin's lymphomas although results are disappointing when it has been used as single agent first-line therapy (Solal-Celigny et al, 1996). In an Intergroup randomised trial, fludarabine resulted in a better response rate than CVP (cyclophosphamide, vincristine and prednisolone), but this did not translate into improved time to treatment failure or overall survival (OS) (Marcus et al, 2002).…”
mentioning
confidence: 99%
“…This degree of myelosuppression is consistent with other front-line, Phase II studies of single-agent 2-CdA or fludarabine in patients with indolent NHL, in which from 36% to 59% of patients and from 6% to 21% of patients experience grade 3 or 4 neutropenia and thrombocytopenia, respectively. 4,5,36,37 Antibiotic prophylaxis was not required on the current trial, and no grade 3 or 4 opportunistic infections were reported. The use of such prophylaxis may be more critical in previously treated patients, particularly for those patients who already have received nucleoside analogs or who are receiving concomitant steroids.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7][8][9] These results also compare favorably with front-line fludarabine in indolent NHL, in which OR rates from 62% to 84% and CR rates from 15% to 47% have been reported. [33][34][35][36][37] Although the median remission duration in this trial was only 1.9 years, 6 patients have ongoing responses that range from 5.9 years to 11 years. These patients did have fewer adverse prognostic features at the time of study entry, and 3 of these 6 patients had SLL, suggesting that further evaluation of 2-CdA in this NHL subtype may be warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Fludarabine exhibits a high level of efficacy in this setting, with overall response rates of approximately 60 -70% and complete remission (CR) rates of approximately 30% (Table 2). 21,59 Encouraging data regarding PFS have also been obtained; Coiffier et al 59 reported a 2-year PFS rate of 49% in patients receiving fludarabine monotherapy. In a randomized trial, Hagenbeek et al 19 compared fludarabine with CVP in patients with low-grade NHL and found that the overall response rate associated with fludarabine use was significantly higher (68% vs. 51% [P ϭ 0.001]; CR rate, 38% vs. 15%); however, the observed median time to progression did not differ significantly between the two treatment arms (21 months vs. 15 months [P ϭ 0.24]), and the median OS had not yet been reached at the time of that report.…”
Section: Efficacy Of Fludarabine Fludarabine As a Single Agentmentioning
confidence: 99%